Increased Beat-to-Beat Variability of T-Wave Heterogeneity Measured From Standard 12-Lead Electrocardiogram Is Associated With Sudden Cardiac Death: A Case–Control Study - Hekkanen, Jenni J.; Kenttä, Tuomas V.; Haukilahti, Mira Anette E.; Rahola, Janne T.; Holmström, Lauri; Vähätalo, Juha; Tulppo, Mikko P.; Kiviniemi, Antti M.; Pakanen, Lasse; Ukkola, Olavi H.; Junttila, M. Juhani; Huikuri, Heikki V.; et al. (Frontiers in Physiology, 2020)
Introduction: The prognostic significance of beat-to-beat variability of spatial heterogeneity of repolarization measured from standard 12-lead ECG is not well understood. Methods: We measured the short-term variability of repolarization parameters, such as T-wave heterogeneity in leads V4-6 (TWH) and QT interval (QT), from 5 consecutive beats of previously recorded standard 12-lead ECG in 200 victims of unexpected sudden cardiac death (SCD) confirmed to be due to complicated atherosclerotic coronary artery disease (CAD) in medico-legal autopsy and 200 age- and sex-matched controls with angiographically confirmed CAD. The short-term variability of repolarization heterogeneity was defined as the standard deviation (SD) of the measured repolarization parameters. All ECGs were in sinus rhythm and no premature ventricular contractions were included in the measured segment. Results: TWH-SD and QT-SD were significantly higher in SCD victims than in subjects with CAD (6.9 (SD 5.6) µV vs. 3.8 (SD 2.6) µV, p=1.8E-11; 8.3 (SD 13.1) ms vs. 3.8 (SD 7.1) ms, p=0.00003, respectively). After adjusting in the multivariate clinical model with factors, such as diabetes, RR-interval and beta blocker medication, TWH-SD and QT-SD retained their significant power in discriminating between the victims of SCD and the patients with CAD (p=0.00003, p=0.006, respectively). TWH-SD outperformed QT-SD in identifying the SCD victims among the study subjects (area under the curve in the receiver operating characteristics curve 0.730 vs. 0.679, respectively). Conclusions: Increased short-term variability of repolarization heterogeneity measured from standard 12-lead ECG is associated with SCD.